2020
DOI: 10.1002/ece3.6815
|View full text |Cite
|
Sign up to set email alerts
|

Relative influence of wild prey and livestock abundance on carnivore‐caused livestock predation

Abstract: Conservation conflict over livestock depredation is one of the key drivers of large mammalian carnivore declines worldwide. Mitigating this conflict requires strategies informed by reliable knowledge of factors influencing livestock depredation. Wild prey and livestock abundance are critical factors influencing the extent of livestock depredation. We compared whether the extent of livestock predation by snow leopards Panthera uncia differed in relation to densities of wild prey, livestoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 84 publications
(108 reference statements)
1
14
0
Order By: Relevance
“…We used a stratified random sampling design based on an occupancy survey for our camera trap-based abundance estimation, and estimated snow leopard density for an area that was 1.5 times larger than the cumulative size of the study areas of all the previously published studies put together (Chetri et al, 2019;Khanal et al, 2020;Suryawanshi et al, 2019). Johansson et al (2016) showed that 40%…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used a stratified random sampling design based on an occupancy survey for our camera trap-based abundance estimation, and estimated snow leopard density for an area that was 1.5 times larger than the cumulative size of the study areas of all the previously published studies put together (Chetri et al, 2019;Khanal et al, 2020;Suryawanshi et al, 2019). Johansson et al (2016) showed that 40%…”
Section: Discussionmentioning
confidence: 99%
“…We assessed snow leopard abundance in a large landscape of over 26,112 km 2 comprising the entire snow leopard habitat in the state of Himachal Pradesh in India (Figure 1). The size of our study area was one and half times the size of the entire area covered cumulatively by all published snow leopard population estimation studies conducted so far across its range (Chetri et al 2019;Khanal et al, 2020;Suryawanshi et al, 2019). The primary goal of our study was to demonstrate a two-step sampling approach for estimating the population of snow leopards at a large spatial scale.…”
Section: Introductionmentioning
confidence: 99%
“…We found that livestock consumption by snow leopards (both per sample RRA and total amount) was strongly correlated with local livestock biomass, but not with livestock density (Figure 5). Livestock density is a common index used to assess wild predator depredation response to domestic prey availability (Chetri et al, 2017;Pimenta et al, 2018;Khanal et al, 2020). However, we argue that spatial distribution of livestock, compared with wild prey, is more heterogeneous and often clustered near resources and shelters, thus making average density across large areas an inappropriate measure of livestock availability.…”
Section: Prey Preference and Livestock Consumptionmentioning
confidence: 97%
“…This study indicated high detection probabilities at 0.94 and 0.91 for O1 and O2 respectively, comparable to those of Thinely et al (2018). By contrast, Khattak et al (2019) reported lower detection rates in Pakistan's isolated blue sheep population (0.78 and 0.47); Khanal et al (2020) estimated detection rates of 0.67 and 0.70 in Lower Dolpa and 0.78 and 0.75 in the Upper Dolpa sector of Nepal's SPNP. Khanyari et al (2021) reported similar ranges (0.36–0.74) in the central Tien Shan landscape of Kyrgyzstan.…”
Section: Discussionmentioning
confidence: 96%